How to Collaborate Through Teams. (2nd April 2016) - Conderman, Greg
Abstract: Teachers are spending more of their time and making more decisions within teams. Effective teacher-based teams provide academic and behavioral support for students as well as professional development for teachers. Learn how the best teams function .